Change and Continuity in Poland?s Environmental Policy - Andersson, Magnus (Springer Netherlands, 1999)
This book takes a long-term view of environmental policy in Poland, which thus serves as an example to increase our understanding of environmental policy making in general in the former Eastern bloc countries. The perspective adopted also includes the pre-transition period, since the transformation process cannot be understood without reference to the preceding period. The book investigates the driving forces underlying policy changes, both prior to and after the transition, and identifies elements both of change and continuity - topics that have hitherto been neglected in the literature. A change of political system in Poland did not lead to a major change in the thrust of environmental policy: the policy makers adopted a cautious approach to new instruments and institutions during the transition period. What did change with the transition was the implementation aspect: the effectiveness of environmental policy increased dramatically after the abolition of socialism. The rule of law meant that the state administration and the polluters were subordinated to the legal system, thus increasing the power to environmental policy. Readership: Researchers and students interested in the environment and the countries in transition
Keywords: Environment; Environmental Management; Regional and Cultural Studies; Political Science; Environmental Law/Policy/Ecojustice; Environmental Economics; Culture / Study and teaching; Political science; Environmental law; Environmental policy; Environmental management; Environmental economics; Umweltpolitik; Polen